Finite element (FE) analysis of thermal stress in production process of multi-layer lining ladle - Linfang Fang; Fuyong Su; Zhen Kang; Haojun Zhu (Case Studies in Thermal Engineering, 2024)
This paper presented the development of the thermo-mechanical coupling model and simulation analysis of a composite refractory layer ladle. The thermomechanical modeling of the ladle was carried out using the Finite Element Method (FEM), taking into account the joints between the slag line bricks as well as the contact between the composite refractory layers. The temperature and thermal stress characteristics of the overall ladle structure under different transit conditions were investigated using the finite element analysis software ANSYS. We also performed a comparative analysis on the improvement effect of thermal stresses by expansion joints of different sizes. The simulation results were validated with previous studies. The results showed that the installation of expansion joints within a suitable range did not significantly change the thermal expansion characteristics of the refractory lining, but it also reduced the thermal stress level of the lining to a large extent. A larger temperature gradient produced higher thermal stresses, and in the direction of the ladle height, the more downward the position of its maximum compressive stress was greater. Under different working conditions, compared with the axial and hoop stress, the radial stress was small in magnitude. Axial stress exhibited a greater degree of sensitivity to pressure variations than hoop stress. The developed thermodynamic model considering the full contact between the bricks and the refractory layer gave us a more complete view of the physical field laws inside the ladle.